2015
DOI: 10.1128/iai.03073-14
|View full text |Cite
|
Sign up to set email alerts
|

The Levels of Brachyspira hyodysenteriae Binding to Porcine Colonic Mucins Differ between Individuals, and Binding Is Increased to Mucins from Infected Pigs with De Novo MUC5AC Synthesis

Abstract: c Brachyspira hyodysenteriae colonizes the pig colon, resulting in mucohemorrhagic diarrhea and growth retardation. Fecal mucus is a characteristic feature of swine dysentery; therefore, we investigated how the mucin environment changes in the colon during infection with B. hyodysenteriae and how these changes affect this bacterium's interaction with mucins. We isolated and characterized mucins, the main component of mucus, from the colon of experimentally inoculated and control pigs and investigated B. hyodys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
91
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(102 citation statements)
references
References 47 publications
10
91
1
Order By: Relevance
“…We previously reported that B. hyodysenteriae infection causes changes in the mucin environment that are characterized by a disorganized mucus structure and massive mucus induction with de novo expression of MUC5AC and increased production of MUC2 in the colon (12). The results from the present study show that several factors from the immune system are differentially expressed in the pig colon during B. hyodysenteriae infection.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…We previously reported that B. hyodysenteriae infection causes changes in the mucin environment that are characterized by a disorganized mucus structure and massive mucus induction with de novo expression of MUC5AC and increased production of MUC2 in the colon (12). The results from the present study show that several factors from the immune system are differentially expressed in the pig colon during B. hyodysenteriae infection.…”
Section: Discussionsupporting
confidence: 58%
“…1A). Pig 1 presented milder clinical signs of dysentery and an absence of de novo MUC5AC expression and increased MUC2 production; thus, this animal produced mucus similar to that observed in the control pigs (Table 1) (12). IL-17A expression correlated with MUC5AC mRNA levels (r ϭ 0.8, P ϭ 0.01) and the MUC5AC protein amount in the colon tissue (Table 1) (r ϭ 0.8, P ϭ 0.01).…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations